Impact of Clinical Characteristics and Statins on Coronary Plaque Progression by Serial Computed Tomography Angiography. (March 2020) - Smit, Jeff M.; van Rosendael, Alexander R.; El Mahdiui, Mohammed; Neglia, Danilo; Knuuti, Juhani; Saraste, Antti; Buechel, Ronny R.; Teresinska, Anna; Pizzi, Maria N.; Roque, Albert; Poddighe, Rosa; Mertens, Bart J.; et al.
Abstract : Background: Progression of coronary artery disease using serial coronary computed tomography angiography (CTA) is of clinical interest. Our primary aim was to prospectively assess the impact of clinical characteristics and statin use on quantitatively assessed coronary plaque progression in a low-risk study population during long-term follow-up. Methods: Patients who previously underwent coronary CTA for suspected coronary artery disease were prospectively included to undergo follow-up coronary CTA. The primary end point was coronary artery disease progression, defined as the absolute annual increase in total, calcified, and noncalcified plaque volume by quantitative CTA analysis. Results: In total, 202 patients underwent serial coronary CTA with a mean interscan period of 6.2±1.4 years. On a per-plaque basis, increasing age (β=0.070; P =0.058) and hypertension (β=1.380; P =0.075) were nonsignificantly associated with annual total plaque progression. Male sex (β=1.676; P =0.009), diabetes mellitus (β=1.725; P =0.012), and statin use (β=1.498; P =0.046) showed an independent association with annual progression of calcified plaque. While hypertension (β=2.259; P =0.015) was an independent determinant of noncalcified plaque progression, statin use (β=−2.178; P =0.050) was borderline significantly associated with a reduced progression of noncalcified plaque. Conclusions: Statin use was associated with an increased progression of calcified coronary plaque and a reduced progression of noncalcified coronary plaque, potentially reflecting calcification of the noncalcified plaque component. Whereas hypertension was the only modifiable risk factor predictive of noncalcified plaque progression, diabetes mellitus mainly led to an increase in calcified plaque. These findings could yield the need for intensified preventive treatment of patients with diabetes mellitus and hypertension to slow and stabilize coronary artery disease progression and improve clinical outcome. Abstract : Supplemental Digital Content is available in the text.